2006
DOI: 10.1021/jp064745o
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Hydrogen Isotopes on Micro- and Mesoporous Adsorbents with Orderly Structure

Abstract: The equilibrium and dynamic adsorption data of H(2) and D(2) on different micro- and mesoporous adsorbents with orderly structure including 3A, 4A, 5A, Y, and 10X zeolites; carbon CMK-3; silica SBA-15; and so forth were collected. Critical effect of the nanodimension of adsorbents on the adsorption behavior of hydrogen and its isotopes is shown. The highest adsorption capacity was observed at pore size 0.7 nm, but equal or even larger isotope difference in the equilibrium adsorption was observed at larger pore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 17 publications
4
48
0
Order By: Relevance
“…As has been stated previously, this material has an extremely large surface area (3103 m 2 /g), which is particularly beneficial for achieving large excess H 2 gravimetric uptake values. Furthermore, this material has a large cumulative pore volume (>1 cm 3 ) and small pore diameters (predominantly e3 nm). Both of these characteristics are ideal for creating a material optimized for H 2 storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been stated previously, this material has an extremely large surface area (3103 m 2 /g), which is particularly beneficial for achieving large excess H 2 gravimetric uptake values. Furthermore, this material has a large cumulative pore volume (>1 cm 3 ) and small pore diameters (predominantly e3 nm). Both of these characteristics are ideal for creating a material optimized for H 2 storage.…”
Section: Resultsmentioning
confidence: 99%
“…Among this class of materials, it is thought that microporous carbons have the pore diameters best suited for H 2 storage. 3 However, it has proven nontrivial to achieve both the large surface areas and the micropore diameters necessary for optimized H 2 storage. 4 Many methods, such as activation 5 and inorganic 6 or organic 7 templating, have been utilized to achieve such porous materials; however, no material has mastered both a large surface area and a small pore diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers (Strobel et al 2006;Nijkamp et al 2001;Chu et al 2006;Castro et al 2010) have reported a linear dependence between the adsorption capacity of carbon materials and the storage capacity. Frost and Snurr (2007) showed in a theoretical study that, in molecular organic frameworks (MOF), a linear relationship exists between the surface area and the adsorption capacity at intermediate pressures and a linear relationship between the free volume and the storage density at higher pressures.…”
Section: Physisorption Of Hydrogen In Nanoporous Structuresmentioning
confidence: 99%
“…Hydrogen adsorption has been studied for a wide range of porous carbons, [40, silicas, [63,90] aluminas, [63] zeolites, [91][92][93][94][95][96][97] porous polymers, [98][99][100][101][102][103][104][105][106][107] COFs [108][109][110][111][112] and MOFs. [21,27,36,38,39,50,51,54,57,58, Hydrogen adsorption measurements for porous materials carried out at pressures up to 1 bar provide data for calculating the isosteric enthalpies of adsorption at zero surface coverage, which is a measure of the hydrogen surface interaction.…”
Section: Hydrogen Adsorption Capacity Studiesmentioning
confidence: 99%
“…The smallest micropores contribute more to the hydrogen adsorption uptake at 1 bar than larger pores. [40,77,190] Figure 4.7 shows the variation of hydrogen uptakes at 1 bar and 77 K vs BET surface area for carbons, [40,63,65,67,68,70,71,74,76,78,83,89] silicas, aluminas, zeolites, [63,70,[92][93][94]96] porous polymers, [98][99][100]104] COFs [108,111,112] and MOFs. [21,27,36,38,39,51,57,58,[186][187][188] A spread of results is observed but [40,63,65,67,68,74,[76][77][7...…”
Section: Hydrogen Adsorption Capacity Studiesmentioning
confidence: 99%